The role of CCTV’s in detecting traffic crimes and accidents in Hódmezővásárhely (Academic Journal of Internal Affairs, 2016)
The author provides an overview of an analysis of how CCTV’s have been used in detecting traffic related criminal activity and accidents in the Hungarian town of Hódmezővásárhely.
Keywords: CCTV; detection; Hódmezővásárhely